Histopathological spectrum of oral squamous cell carcinoma in Naswar users: Correlation with duration, age and site - Iqbal, Fatima; Bashir, Nasiha; Maryam, Hoor; Ahmad, Sajjad (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the relationship of clinico- pathological parameters with the histopathological spectrum of oral squamous cell carcinoma in a high-risk population. Method: The prospective, cross-sectional study was conducted from January 2019 to September 2022 in the Khyber Pakhtunkhwa province of Pakistan, and comprised histologically confirmed cases of oral squamous cell carcinoma with a history of consumption of Naswar from different hospitals. The duration of use, age, site and histopathological features were recorded, and their association was explored. Data was analysed using SPSS 19. Results: Of the 80 patients with mean age 56.98±12.94 years at diagnosis, 59(73%) were males and 21(26%) were females. Buccal mucosa was the predominant site of involvement 28(35%). Histologically, the most common presentation was well-differentiated squamous cell carcinoma 63(78.7%). The association of age and use duration with the histopathological pattern of oral squamous cell carcinoma was statistically non-significant (p>0.05). Conclusion: There was no significant association of age and prolonged Naswar use with histopathological patterns of oral squamous cell carcinoma. Keywords: Histopathology, Oral squamous cell carcinoma, Risk factors, Smokeless tobacco.